Libertatea de exprimare si deplatformarea (Freedom of expression and deplatforming) - Preda, Adina (Polirom, 2021)
Some complain that either the right to freedom of speech or expression or people’s freedom is being restricted in recent times by calls for no platforming certain individuals. This paper aims to argue that such complaints are misplaced. The right to freedom of speech, will be argued, is best understood as a right against governments and social censorship does not restrict or infringe on this right. First, I will clarify the ways in which this right can be understood, namely either as a Hohfeldian liberty or an immunity. The former can be held against other people but does not correlate with a duty that they refrain from criticising the content of any speech. So demands for refraining from expressing certain opinions are not restrictions of the right to freedom of speech but rather demands for self-censorship, which is not a restriction of our freedom of expression, even if we may feel unfree to say things. The latter is held against a government and is usually a specific instance of freedom of expression, which is freedom of the press. But nobody thinks that the freedom of the press should be unrestricted. There are laws against libel, slander, defamation as well as complex professional ethics standards that journalists must comply with and I take it that a democratic society would not want to do away with those. So, again, it is just a misconception that the freedom of the press should be unlimited and that the press should be immune from the powers of the state. I then consider the claim that no platforming diminishes empirical (rather than deontic) freedom. I argue that this claim does not withstand scrutiny if we adopt a negative conception of freedom. No platforming may diminish freedom of choice but, inasmuch as this is undesirable, it should be compared to the freedom of choice of the members of communities offended or harmed by the speech in question.
Alegeri morale (Moral Choices)